Comparing the ROI of Potential Candidates for Weekly Options Trading using Long Straddle Strategy. - Noor Syahirah, Noor Kifli (Universiti Malaysia Sarawak (UNIMAS), 2019)
Financial derivatives market (both exchange traded and overthe counter) is the most innovative investment sector. Novel hedging and arbitrage strategies are emerging daily, with very complex payout scenarios and multi-factor credit and market risk exposures. Nevertheless, financial options remain popular trading tools, as they afford the option buyer the element of transaction choice in the future. This paper provides an overview of fundamental option trading concepts as well as a wide range of most popular trading strategies with their applications, risks and benefits.